2004
DOI: 10.1017/s0954579404044554
|View full text |Cite
|
Sign up to set email alerts
|

Emotion understanding in postinstitutionalized Eastern European children

Abstract: To examine the effects of early emotional neglect on children's affective development, we assessed children who had experienced institutionalized care prior to adoption into family environments. One task required children to identify photographs of facial expressions of emotion. A second task required children to match facial expressions to an emotional situation. Internationally adopted, postinstitutionalized children had difficulty identifying facial expressions of emotion. In addition, postinstitutionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
121
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 54 publications
8
121
3
5
Order By: Relevance
“…Institutional environments can have lasting effects on qualitative features of children's emotional development and social cognition (Fries & Pollak, 2004;Yagmurlu, Berument & Celimli, 2005;Camras, Perlman, Fries & Pollak, 2006). Presumably this experience might also alter the course of cognitive or linguistic development.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Institutional environments can have lasting effects on qualitative features of children's emotional development and social cognition (Fries & Pollak, 2004;Yagmurlu, Berument & Celimli, 2005;Camras, Perlman, Fries & Pollak, 2006). Presumably this experience might also alter the course of cognitive or linguistic development.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…For example, it has been shown that the presence of abuse during childhood leads to very different psychological outcomes than does neglect or the absence of affection. Children who have been exposed to early abuse seem to show a heightened sensitivity to negative emotional cues that signify harm or aggression (such as angry faces) [Pollak & Kistler, 2002], whereas neglected children tend to show a different psychological profile characterized by avoiding social interactions altogether or showing indiscriminate friendliness towards all [Wismer Fries & Pollak, 2004]. Part of the reason for these different behavioral profiles may be due to the fact that these early experiences shape the sensitivity of separate neural systems, and thus may have different consequences for psychological function.…”
Section: Similar Psychological Processes Different Neural Substratesmentioning
confidence: 99%
“…From these observations, Bowlby suggested that prolonged separation from a caregiver in early life was likely to lead to various forms of psychopathology in later life. Indeed, recent observations from Eastern European orphanages support this claim; orphans lacking early social ties do not develop normal social or emotional skills and have longlasting problems maintaining social relationships [Wismer Fries & Pollak, 2004].…”
mentioning
confidence: 99%
“…Neglected children may have difficulty in discriminating emotional expression (Fries & Pollak, 2004) and show various attention and social deficits (Turgeon & Nolin, 2004). The lack of emotional interaction during the crucial early period of development can result in poor emotional regulation that may be part of a cascade of adverse neurobiological events rendering a child vulnerable to the effects of later adverse experiences and triggering a vicious cycle towards adult depression.…”
Section: Emotional Neglectmentioning
confidence: 99%